Outcome Evaluation of a Treatment Program for Men with Paraphilic Disorders Convicted of Sexual Offenses: 10-Year Community Follow-up - Páv, Marek; Sebalo, Ivan; Brichcín, Slavoj; Perkins, Derek (International journal of offender therapy and comparative criminology, 2025)
Evidence concerning specific paraphilia treatment effectiveness is limited. We present observation data of 127 men convicted of paraphilic sexual offenses who attended inpatient and outpatient follow-up treatment in Czechia. We collected participants' sociodemographic and treatment-related information, including STATIC-99R scores, and used proportional hazards models to analyze variables' effect on recidivism risk. Within the observation period, the general recidivism and sexual recidivism rates were 33.1% and 16.5%, respectively, and the sexual contact recidivism rate was 4.7%. The total STATIC-99 score for those who re-offended was 5.65 (SD = 2.11) and for those who did not was 3.98 (SD = 2.02). Recidivism risk was 7.52 times higher for those diagnosed with exhibitionism than with pedophilia, sadomasochism, or antisocial personality disorder. General recidivism is comparable to others' findings. We attribute the lower sexual contact recidivism rate to the combined effects of psychological and pharmacological treatment, and higher numbers of non-contact offenses to limited antidepressant use.
Keywords: exhibicionismus; Middle Aged; mužské pohlaví; Adult; mladý dospělý; parafilie; paraphilia; Follow-Up Studies; následné studie; recidivismus; Young Adult; Exhibitionism; Recidivism; Humans; sexuální delikty; STATIC-99; lidé středního věku; Paraphilic Disorders; inpatient forensic treatment; dospělí; recidivism rates; Sex Offenses; exhibitionism; lidé; Male